ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU PRODUK BAWANG GORENG PADA INDUSTRI RUMAH TANGGA â€œUSAHA BERSAMA" DI DESA BULUPOUNTU JAYA KECAMATAN SIGI BIROMARU - Hasrul, Hasrul (JSTT, 2014)
The research aimed at finding out the control of the basic commodity product of fried red onion of Palu variety as the main commodity used at the Home Industry â€œUsaha Bersamaâ€ and analyzing the use of basic commodity to make fried onion.Â  The sample, â€œUsaha Bersamaâ€ in Bulupountu Jaya Village as the place of this research, was stated by using purposive sampling technique.Â  This village was one of the centres for development of red onion variety of Palu and had home industry for producting fried onion in Sigi Regency.Â  Data were collected by using survey and direct observation.Â  The data were analyzed by adopting Economic Order Quantity (EOQ) and Linier Trend Line analyses.Â  The result shows that the optimal purchasing of the basic commodity was 2.192 kilograms per order; then, it was obtained the efficiency of supply restraint cost, 75.262,99 rupiahs (20%).Â  Meanwhile, the result of Linier Trend Line analysis shows that prediction of the basic commodity need from January to December 2013 was 1.423 kilograms for each order.Â  It is suggested that procurement of the basic commodity of Palu red onion variety applied at â€œUsaha Bersamaâ€ could be done by purchasing the commodity with 2.192 kilograms per order and with 8 times a year for the order frequency.